Sarcasm in Sarawakian NgekTsaiArmy Official YouTube Videos - Abdul Wahab, Hamidah; Jackson, Jessica Nuwie (Trends in Undergraduate Research, 2023)
Sarcasm typically uses particular phrases in a figurative sense, and occasionally contains insults or reproaches, which makes it unpleasant to hear. However, in certain context, sarcasm is also used to make remarks, criticism, or advice towards an individual or a group of people, related to an issue. This study analyses the use of sarcasm in NgekTsaiArmy Official YouTube videos, a channel managed by NgekTsai who is a famous social media influencer or vlogger from Sarawak. The method of content analysis is used in analysing data from the utterances of the characters in videos with themes of family, society, education, work, and culture. The data were analysed based on the Speech Act Theory (Searle, 1969). The findings of the study show that there are four types of language acts that exist in the NgekTsaiArmy Official videos, namely assertive, directive, expressive, and commissive. Although this language act contains elements of sarcasm, it is uttered mostly with the aim of making the public aware of current issues, thus providing useful and positive input to the public. In addition, the culture and dialect of the Sarawak Malay community are also highlighted by NgekTsai in a unique way that attracts the attention of its viewers.